Rasgos de personalidad y su relación con episodios depresivos en personas no heterosexuales de la ciudad de Loja, periodo 2018 - 2019 - Pontón Hurtado, Luz María (2019)
Despite the progress in the legal field, the law has changed, but the problem faced by non-heterosexual people in the exercise of their rights entails a series of consequences that have an impact on their mental health. Thus, the purpose of this work was to evaluate and relate personality traits to depressive symptomatology in non-heterosexual people in the city of Loja. The study was carried out following a cross-sectional descriptive-correlational approach, in which 35 self-identified persons were evaluated as lesbians, gays, bisexuals, trans and intersex of the Loja city; the same ones that were selected by non-probabilistic snowball type sampling and / or convenience. As a data collection instrument, Questionnaire 16 FP fifth edition and the Beck-II Depression Inventory were applied. The results demonstrate a significant incidence of mild and moderate depressive episodes, as well as the presence of friendly personality traits in the population, establishing a significant correlation between these variables. Based on the data obtained, a psychotherapeutic intervention plan was designed to promote psychological well-being. Keywords: personality, depression, non-heterosexual people.